IMPLEMENTATION OF MIND MAPPING METHOD COMBINED WITH MAKE A MATCH TECHNIQUES ON COOPERATION ATTITUDE AND STUDENT LEARNING OUTCOMES - Rizki Rahmadhani; Zulkifli Simatupang (Universitas Negeri Medan, 2020)
This study aims to describe the implementation of Biology learning using the Mind Mapping method combined with the Make A Match technique. The study used a descriptive research design. The whole series of research processes are conducted with the standards of graduates, processes standard, and assessment standards applied in the 2013 curriculum. The implementation phase of instruction is done: 1) Measurement of teacher's ability to prepare a lesson plan and implement teaching-learning; 2) The attitude of students cooperation when composing a Mind Mapping on the material of the human excretion system; 3) Measurement of student learning outcomes. Data analysis was done by the descriptive statistic technique, in mean form, standard deviation, frequency distribution, and description of learning recordings. As a result, the teacher can implement well the Biology learning device material of the human excretion system in class XI MIA Lubuk Pakam MAN using the Mind Mapping method combined with the Make A Match technique. The collaboration of students in class XI MIA MAN Lubuk Pakam when composing a Mind Mapping is in a good category. The distribution of mastery learning in class XI MIA MAN Lubuk Pakam after learning the Mind Mapping method combined with Make A Match technique is 76,1% of students reaching completeness and 23,9% unfinished. The learning mastery in the Mind Mapping method combined with the Make A Match technique is higher than the previous daily test.